2021
DOI: 10.21203/rs.3.rs-222733/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting Lactate Dehydrogenase A Improves Radiotherapy Efficacy in Non-Small Cell Lung Cancer: From Bedside to Bench

Abstract: BackgroundLDHA is overexpressed in many kinds of cancer, and associated with poor prognosis. In the current study, we evaluated the prognostic value of LDHA expression in non-small cell lung cancer (NSCLC), and tested whether LDHA inhibition might improve radiotherapy efficacy in NSCLC.MethodsLDHA mRNA expression was investigated in NSCLC patients, using online database and further verified by immunohistochemistry. The prognostic value of LDHA was evaluated using Kaplan-Meier plotter database. In vitro, two NS… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Our previous study [26] has revealed that oxamate, an inhibitor of LDH-A, signi cantly suppressed the proliferation of NSCLC cells, while it exerted a much lower toxicity in normal cells. LDH-A inhibition resulted in ATP reduction and ROS (reactive oxygen species) burst in cancer cells, which lead to apoptosis and G2/M arrest and increase radiosensitivity in NSCLC cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study [26] has revealed that oxamate, an inhibitor of LDH-A, signi cantly suppressed the proliferation of NSCLC cells, while it exerted a much lower toxicity in normal cells. LDH-A inhibition resulted in ATP reduction and ROS (reactive oxygen species) burst in cancer cells, which lead to apoptosis and G2/M arrest and increase radiosensitivity in NSCLC cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of tumor cells to radiation defines the efficacy of radiotherapy. Nevertheless, a growing number of studies have indicated that patients with NSCLC can acquire resistance to radiotherapy, which limits the effects of radiotherapy (5)(6)(7). Therefore, it is crucial to explore the underlying mechanism of radioresistance in NSCLC.…”
Section: Introductionmentioning
confidence: 99%